2020
DOI: 10.3389/fonc.2020.563407
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic Features and Prognosis of BRAF Mutated Colorectal Cancer Patients

Abstract: Background:BRAFV600E mutation is associated with poor prognosis of colorectal cancer (CRC) patients, but the comparison of clinic-pathologic features between V600E and non-V600E mutation was not well-known in CRC patients. The aim of this study is to evaluate the clinical and pathological features, prognostic value of BRAF mutations in CRC.Methods: We conducted a retrospective study to characterize the clinical and pathological features and survival of patients with BRAF mutated CRC. Patients were classified a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…4 B). BRAF mutations have been associated with worse prognosis in diverse cancers [43] , [44] . In CESC, ESCA, STAD, and THCA, BRAF -mutated tumors had significantly higher SP scores than BRAF -wildtype tumors ( P < 0.05) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4 B). BRAF mutations have been associated with worse prognosis in diverse cancers [43] , [44] . In CESC, ESCA, STAD, and THCA, BRAF -mutated tumors had significantly higher SP scores than BRAF -wildtype tumors ( P < 0.05) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Patients with BRAF V600E mutation have been reported to have the worst prognosis among all BRAF mutations [7] [22,23]. Encouragingly, the development of novel targeted therapy has been proved to have fewer side effects and has a more promising e cacy [2].Previous studies have reported that dabrafenib plus trametinib was a new therapy with clinically meaningful anti-tumor activity and a manageable safety pro le in patients with BRAF V600E non-small cell lung cancer (NSCLC).…”
Section: Discussionmentioning
confidence: 99%
“…The Raf murine sarcoma viral oncogene homolog B (BRAF) mutation is detected in 8-10% of metastatic colorectal cancers (mCRCs) and is strongly correlated with patients' poor prognosis [5,6]. It was reported that patients with BRAF V600E mutation showed a poorer outcome than those with non-V600E mutations [7]. Recently, studies on therapies for BRAF-mutated mCRC patients have obtained several advances.…”
Section: Introductionmentioning
confidence: 99%
“…A breakthrough in understanding the pathogenesis of LCH occurred in 2010 when a gain-of-function mutation in B-RAF (V600E) was identified in more than half of LCH patient samples [21]. Similar to in melanoma [22], colon [23], and thyroid cancer [24], BRAF V600E marks poor outcomes. In a series of 315 children with LCH, the B-RAF V600E mutation was correlated with aggressive disease and resistance to chemotherapy [25].…”
Section: Discussionmentioning
confidence: 99%